PENGARUH MODEL PBL TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS 4 PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Prasasti Rahersita Damayanti; Anggit Grahito Wicaksono; Sarafuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the lack of critical thinking skills among fourth-grade students of SDN 1 Sambi in Pancasila education lessons. This is due to the learning that still uses a traditional teacher-centered approach that limits students' active participation in analyzing and solving various problems. This study aims to further examine the effect of the PBL model on critical thinking skills in Pancasila education lessons in the 2024/2025 academic year. This study involved 28 students and used a pre-experimental one-group pretest-posttest design. Data collection techniques include observation, interviews, tests, and documents with instruments that have been tested for validity and reliability, which obtained a Cronbach's Alpha of 0.8224, categorized as reliable data. Data analysis used the Sapphiro Wilk normality test and paired sample T-test hypothesis testing. The results found an average pretest of 62.9982 increased to 85.9896 in the posttest with an average difference of 22.9914 and a sig. 0.000 < 0.05, indicating a significant difference before and after treatment. This finding demonstrates that the implementation of the PBL model significantly improves students' critical thinking skills, as it encourages active involvement, collaborative discussions, contextual problem analysis, and rational decision-making. Therefore, the PBL model is effectively implemented in Pancasila education to optimize the development of critical thinking skills in elementary schools.